Analisis Perkembangan Karakter Anak Usia Dini di Kelas 1 SD Negeri Kampung Baru 1 Melalui Pembiasaan Sikap Jujur: Penelitian - Rahmawati Eka Saputri; Alya Nazhifah; Evra Destia Hijas Ayyasy (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In childhood, character building plays a very important role in modern education because it is an effort to shape the character of the younger generation. The purpose of this journal is to explain the method to develop character and foster honesty in young children through honest habits. The method used in this study is qualitative description and assisted by document study, where data collection is done through document analysis. This study shows that learning centers function as effective tools to strengthen students' characters, focusing on values ​​such as empathy, responsibility, and. The results of the discussion reveal that implementing honest habits can instill honesty honesty in children, considering that they are the next generation who need to be educated with a balance between knowledge and character. Implementing an honest attitude can also develop an anti-corruption attitude and build a foundation of character for children when they grow up in an environment that encourages honest habits.